Alkane and PAH provenance and potential bioavailability in coastal marine sediments subject to a gradient of anthropogenic sources in British Columbia, Canada - Yunker, Mark B.; Macdonald, Robie W.; Ross, Peter S.; Johannessen, Sophia C.; Dangerfield, Neil (Organic geochemistry, 2015)
•The BC coast has three distinct hydrocarbon source and sediment transport regimes.•Remote sediments have low petrogenic/pyrogenic input, with no anthropogenic input.•PAHs in sediments likely have low bioavailability on most of the coast.•Urban sediments show PAHs from vehicle emissions and fossil fuel discharge.•PAHs are likely fully bioavailable in the vicinity of large urban areas. Marine coastal areas of British Columbia, Canada are subject to a gradient of increasing anthropogenic sources from pristine areas in the north to the more urbanised areas of the south. Along the gradient, the relative contributions of polycyclic aromatic hydrocarbons (PAHs) from multiple natural and anthropogenic sources are not well understood, but concerns linger about bioavailability and consequent risks to marine biota. Composition patterns and principal components analysis (PCA) models for surface sediment and core samples collected along this transect indicate that samples from the urbanised Vancouver area have the highest proportions of tricyclic terpane, hopane and sterane biomarkers, UCM (unresolved complex mixture), the alkyl fluoranthene/pyrene and benz[a]anthracene/chrysene series and most parent PAHs. Those from Hecate and Queen Charlotte Straits and other locations in the Strait of Georgia have, on the other hand, higher proportions of the resolved alkanes, and petrogenic alkyl naphthalene, fluorene, dibenzothiophene and phenanthrene/anthracene series. PAH ratios clearly indicate a predominance of combustion sources for the four ring and higher parent PAHs for all the sediments. Most samples have values close to the biomass/solid fuel and liquid fuel combustion borderline for ratios of the major PAHs, but liquid fuel combustion input dominates closer to urbanised locations. Ratios also suggest similar pyrogenic and petrogenic inputs between central Hecate Strait and reference sediments from Hecate Strait through to Queen Charlotte Strait, which indicates that biomass combustion and immature coal formations are the major putative respective sources for the reference areas. Alkyl PAH ratios for the C3 and C4 naphthalenes, C2 and C3 phenanthrenes and 3- and 2-methylchrysene, reflecting terrigenous/vascular plant sources and petroleum maturity, exhibit marked differences between Comox bituminous coal and Alberta Sweet Mixed Blend (ASMB) oil and reveal that the petrogenic input in all of the sediments is non-biodegraded. Ratios of these alkyl PAHs with multiple substituents indicate that the sediment samples in the northern Strait of Georgia closest to the Comox coal field receive relatively constant input of eroded coal, while those in the southern Strait of Georgia and Vancouver Harbour show a composition closest to ASMB oil. PAHs associated with liquid fossil fuel combustion and petroleum discharges adjacent to urbanised areas are expected to be fully bioavailable to marine food webs, while the char from biomass combustion and coal from immature deposits in more remote areas would have limited bioavailability. This implies that biota in remote areas of Hecate Strait/Queen Charlotte Sound are likely not adapted to the presence of oil and thus would be more sensitive to exposure to spilled oil than those in the more impacted environments in southern British Columbia.